Calcium intake and hip fracture risk: a meta-analysis of prospective cohort studies - Wang, Dong (Int J Clin Exp Med, 2015)
It has been suggested that the amount of calcium intake may influence hip fracture incidence. However, the results of the researches in this regard are inconsistent. We performed this meta-analysis to estimate the association between calcium intake and hip fracture risk. Prospective cohort studies on calcium intake and hip fracture risk were identified by searching databases from the period 1960 to 2014. Results from individual studies were synthetically combined using STATA 11 software. The results indicated that a total of 8 prospective cohort studies were included in our meta-analysis, involving 2,435 cases and 267,759 participants. The combined relative risk (RR) of hip fracture for highest compared with lowest amount calcium intake was 0.97 (95% confidence interval [CI]: 0.89-1.07). Little evidence of publication bias was found. In conclusion, this meta-analysis provides evidence of no association between calcium intake and hip fracture risk. However, this finding is based on only a limited number of included studies.